A framework of computer vision-enhanced microfluidic approach for automated assessment of the transient sickling kinetics in sickle red blood cells - Qiang, Yuhao; Xu, Mengjia; Pochron, Mira Patel; Jupelli, Madhulika; Dao, Ming (Frontiers in Physics, 2024)
The occurrence of vaso-occlusive crisis (VOC) greatly depends on the competition between the sickling delay time and the transit time of individual sickle cells, i.e., red blood cells (RBCs) from sickle cell disease (SCD) patients, while they are traversing the circulatory system. Most drugs for treating SCD work by inhibiting the polymerization of sickle hemoglobin (HbS), effectively delaying the sickling process in sickle cells (SS RBCs). Many previous studies on screening anti-sickling drugs, such as voxelotor, rely on invitro testing of sickling kinetics, often conducted under prolonged deoxygenation for up to one hour. However, since the microcirculation of RBCs typically takes less than one minute, the results of these studies may be less accurate and less relevant for in vitro-in vivo correlation. In our current study, we introduce a computer vision-enhanced microfluidic framework designed to automatically capture the transient sickling kinetics of SS RBCs within a one-minute timeframe. Our study has successfully detected differences in the transient sickling kinetics between vehicle control and voxelotor-treated SS RBCs. This approach has the potential for broader applications in screening anti-sickling therapies.